2021
DOI: 10.1007/s10459-021-10080-9
|View full text |Cite
|
Sign up to set email alerts
|

Improving medical residents’ self-assessment of their diagnostic accuracy: does feedback help?

Abstract: When physicians do not estimate their diagnostic accuracy correctly, i.e. show inaccurate diagnostic calibration, diagnostic errors or overtesting can occur. A previous study showed that physicians’ diagnostic calibration for easy cases improved, after they received feedback on their previous diagnoses. We investigated whether diagnostic calibration would also improve from this feedback when cases were more difficult. Sixty-nine general-practice residents were randomly assigned to one of two conditions. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…In another study, more than half of paediatricians reported diagnostic error at least once or twice a month, and they made harmful errors at least once or twice a year [ 28 ]. Further, a study in the Netherlands reported diagnostic accuracy of 0.42 among medical residents, scored as either 0 (incorrect), 0.5 (partially correct) or 1 (correct) [ 29 ]. With 96.7% of allergic rhinitis, 95.7% of laryngopharyngeal reflux and 87.0% of ear wax impaction missed by non-ENT clinicians in our study, most of the patients with ENT conditions are likely inappropriately treated with the wrong medication and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, more than half of paediatricians reported diagnostic error at least once or twice a month, and they made harmful errors at least once or twice a year [ 28 ]. Further, a study in the Netherlands reported diagnostic accuracy of 0.42 among medical residents, scored as either 0 (incorrect), 0.5 (partially correct) or 1 (correct) [ 29 ]. With 96.7% of allergic rhinitis, 95.7% of laryngopharyngeal reflux and 87.0% of ear wax impaction missed by non-ENT clinicians in our study, most of the patients with ENT conditions are likely inappropriately treated with the wrong medication and surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Kuhn et al found that feedback made physicians more uncertain of themselves, resulting in an increase in underconfidence, while Nederhand et al observed the opposite effect. 43 , 44 …”
Section: Discussionmentioning
confidence: 99%
“…42 As a result, further unnecessary examinations and tests are carried out, lengthening the diagnostic process. 43 The extent to which additional training helps mitigate underconfidence is unclear. Kuhn et al found that feedback made physicians more uncertain of themselves, resulting in an increase in underconfidence, while Nederhand et al observed the opposite effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance feedback in clinical practice can be as simple as determining if the patient’s treatment was successful or not; information feedback expands on that and could include additional information such as what treatment was ultimately successful or which follow-up tests or results provided further insights. Despite the fact that research specifically concerning calibration and feedback on the diagnostic process remains scarce, previous studies have shown that performance feedback could improve calibration on easy clinical cases (Nederhand et al, 2018 ) but not on difficult cases (Kuhn et al, 2022 ). It has been suggested that information feedback is needed to improve the diagnostic process (Archer, 2010 ; Ryan et al, 2020 ), though evidence for its effects remains limited (Kornegay et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%